LITERASI MEDIA DIGITAL GENERASI Z (STUDI KASUS PADA REMAJA SOCIAL NETWORKING ADDICTION DI JAKARTA) - Riyodina G. Pratikto; Shinta Kristanty (Communication, 2018)
Generation Z is a generation that is active in the use of the internet, they accept social media as something that is taken for granted, with the characteristics of this generation of Z, this generation will be a generation that plays an important role in the development of the State of Indonesia. The problem is that the Z generation of social media users is dominated by teenagers, the negative impact of excessive use of social media by teenagers can lead to addictive behavior which is referred to as social networking addiction. This behavior is caused by various things, from the lack of parental supervision to the lack of digital media literacy in adolescents, as well as to adolescents in Jakarta, especially in the Pesanggerah region, South Jakarta. Based on these problems, the purpose of this study was to find out how digital media literacy in using social media by teenagers in Jakarta belongs to social networking addiction at the level of technical skills, crtitical understanding and communicative abbilities. This study uses concepts related to media literacy, digital media literacy, characteristics of social media, social networking addiction and Generation Z. The research method used is case-1 case study, qualitative approach, data obtained by in-depth interviews and participant observation, as well as data Secondary sources are related documents, books and mass media. The results of this study were the informants were in a state of digital media literacy that was not optimal, at the technical skill level the informants were able to use social networking, but did not understand the negative impact if using it was too active. At the critical understanding level, the informants did not understand the function, how to sort the contents, and the application of the ITE Law, at the level of communicative abbilities the informants did not select their followers, so they often received negative content or negative comments.